اثر استخدام تكنولوجيا الاتصال على الاداء الوظيفي بالمؤسسات العمومية الجزائرية - بطايب, حبيبة (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
جاءت إشكالية هذه الدراسة الموسومة "بأثر استخدام تكنولوجيا الاتصال داخل المؤسسة الجزائرية في تحسين الأداء الوظيفي ، و بالتحديد لدى موظفي مديرية أملاك الدولة لولاية مستغانم ، باعتبار أن الموظفين يساهمون بشكل كبير في تحقيق أهداف المؤسسة و ذلك من خلال استخدام تكنولوجيا الاتصال، فهو يعتبر أساس نجاح المؤسسات و تقدمها، و من هذا المنطلق فان الإشكالية هذه الدراسة تندرج تحتها التساؤل الرئيسي الآتي: إلى آي درجة يمكن ان تؤثر تكنولوجيا الاتصال في تحسين الأداء الوظيفي لموظفي مديرية أملاك الدولة لولاية مستغانم؟ حيث اعتمدنا على المنهج المسحي بتوظيف أداتي الملاحظة والاستبيان التي تضمنت ثلاثة محاور، ووزعت على عينة مقدرة بمائة 100 مفردة. بعد إجراء الدراسة الميدانية على موظفي مديرية أملاك الدولة لولاية مستغانم توصلنا إلى مجموعة من النتائج أهمها: - المديرية تعتمد على تكنولوجيا الاتصال لكن بدرجة متوسطة كما لا يتم توظيف نظام المعلومات كما يعتمدون على المواقع التواصل الاجتماعي لأداء أعمالهم. - مشاكل التدريب هي من أهم العوائق التي تعرقل أدائهم في علاقاتهم مع تكنولوجيا الاتصال الحديثة .
دراسة ميدانية على عينة من الموظفين بمديرية املاك الدولة بمستغانم
We aimed to explore the impact of using communication technology within Algerian institutions on improving job performance, specifically among the employees of the Directorate of State Property in the Wilaya of Mostaganem. Recognizing that employees significantly contribute to achieving institutional goals through the use of communication technology, which is a cornerstone of institutional success and progress, this study seeks to answer the following primary question: To what extent can communication technology improve the job performance of employees at the Directorate of State Property in the Wilaya of Mostaganem?. We employed the survey method, utilizing observation and a questionnaire that included three main sections and was distributed to a sample of 100 individuals. After conducting the field study on the employees of the Directorate of State Property in the Wilaya of Mostaganem, we arrived at several findings, the most important of which are: - The Directorate relies on communication technology to a moderate degree and does not significantly employ information systems. They also rely on social media to perform their tasks. - Training issues are among the major obstacles hindering their performance in relation to modern communication technology.
Keywords: Public Institution, Communication Technology, Job Performance, Directorate of State Property.; المؤسسة العمومية، تكنولوجيا الاتصال، الأداء الوظيفي، مديرية أملاك الدولة